2014
DOI: 10.5114/pdia.2014.40937
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to lidocaine injections: comparison of patient history with skin testing in five patients

Abstract: IntroductionTrue allergy to local anesthetics, especially lidocaine, is uncommon. Most adverse reactions to this group of medications are classified as psychomotor, autonomic or toxic. In the case of suspected hypersensitivity to local anesthetics, skin testing is considered to be a useful tool – patch tests and intradermal tests for delayed hypersensitivity and skin prick tests and intradermal tests for immediate reactions. There is a particular need for such a diagnostic procedure, as patients suspected of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
0
20
0
2
Order By: Relevance
“…Dostupni podaci ukazuju da se skoro na svaki amidni lokalni anestetik u praksi pojavljuje alergijska reakcija, sa određenom rastućom stopom [29][30][31][32][33][34][35][36] . U slučaju sumnje na alergiju na lokalne anestetičke rastvore, preporučuje se primena čistog lokalnog anestetika, bez prisustva stabilizatora koji je mogući antigen, ili upotreba drugog anestetika.…”
Section: Allergic Reactions To Local Anestheticsunclassified
See 1 more Smart Citation
“…Dostupni podaci ukazuju da se skoro na svaki amidni lokalni anestetik u praksi pojavljuje alergijska reakcija, sa određenom rastućom stopom [29][30][31][32][33][34][35][36] . U slučaju sumnje na alergiju na lokalne anestetičke rastvore, preporučuje se primena čistog lokalnog anestetika, bez prisustva stabilizatora koji je mogući antigen, ili upotreba drugog anestetika.…”
Section: Allergic Reactions To Local Anestheticsunclassified
“…Available data indicate that almost every amide local anesthetic in practice causes allergic reaction, with a specific growing pace [29][30][31][32][33][34][35][36] . In the case of suspected allergy to the local anesthetic solutions use of pure local anesthetic is recommended, without the presence of a stabilizer which is a potential antigen, or use of a different anesthetic.…”
Section: Allergic Reactions To Local Anestheticsmentioning
confidence: 99%
“…In cases where a true allergy to the local anaesthetic agent is present, it is most commonly a reaction to the common metabolic product of ester local anaesthetics called para‐amino benzoic acid. As this is a common metabolite, cross‐reactivity between different esters occurs and an allergy to one ester eliminates the possibility of the use of another . Allergic reactions to amide dental local anaesthetics are exceedingly rare and, in contrast to esters, an allergy to one amide does not necessarily rule out the use of another (Table )…”
Section: Introductionmentioning
confidence: 99%
“…Once an adverse reaction occurs in the dental office, it is important that its cause is thoroughly examined. Although a true allergy to local anaesthetic is rare, thorough investigation and accurate diagnosis can protect the patient from a future severe, potentially life‐threatening event . On the other hand, investigation may also allow for the identification of allergy to preservatives, latex or a physiological/psychogenic manifestation that might have led to the observed reaction .…”
Section: Introductionmentioning
confidence: 99%
“…Lidocaine toxicity and anaphylaxis is rare but unfortunately lethal insult is sometimes reported in outpatient clinics. 4 Although use of epinephrine especially in cardiovascular patients can suddenly raises the blood pressure and heart rate, 6,7 but some studies have shown that the amount of epinephrine that is usually added to lidocaine as a local anesthesia is safe and has no considerable effect on the cardiac parameters. 8 However, epinephrine dosage should be minimized, for patients with significant cardiovascular disease, in particular ischemic heart disease.…”
mentioning
confidence: 99%